Impacts of social restrictions on mental health and health behaviours of individuals with multimorbidity during Covid-19 pandemic - Valérie Chauvin; Resti Tito H Villarino; Paquito Bernard; Hanan Yazbek; Laurence Kern; Marie Hokayem; Lama Mattar; Gayatri Kotbagi; Melissa Rizk; Yannick Morvan; Aurélie Baillot; Ahmed Jérôme Romain (Journal of Multimorbidity and Comorbidity)
Background Social restrictions and their possible impact on lifestyle make people with multimorbidity (≥2 co-existing chronic conditions) more vulnerable to poor perceived mental health and health behaviours modifications during the COVID-19 pandemic. Objective To understand the mental health status and health behaviour modifications among individuals with multimorbidity during different levels of COVID-19 social restrictions. Methods Longitudinal multinational cohort study consisting of two online questionnaires with its first wave taken place while social restrictions were imposed (May 2020), and its second wave with less social restrictions in place (November 2020). Including 559 participants (wave 1) and 147 participants from wave 1 (wave 2) with an average age of 34.30±12.35 and 36.21±13.07 years old. Mostly females living in Canada, France, India and Lebanon. Results The prevalence of multimorbidity was 27.68% (wave 1) and 35.37% (wave 2). While social restrictions were imposed, people with multimorbidity were 2 to 3 times more likely to experience psychological distress, depressive symptoms, increased stress or isolation than those without multimorbidity. Health behaviours were also modified during this period with people with multimorbidity being more likely to reduce their physical activity and increased their fruit and vegetable consumption. In wave 2, regardless of multimorbidity status, sexual desire continuously decreased while stress and psychological distress increased. Conclusion Mental health and health behaviours modifications occurred while social restrictions were imposed and people with multimorbidity were more severely impacted than those without multimorbidity, indicating a need for a more adapted approach of care during socially restrictive periods for this population.